Model free kinetics coupled with finite element method for curing simulation of thermosetting epoxy resins - Tao, Qi; Pinter, Gerald; Antretter, Thomas; Krivec, Thomas; Fuchs, Peter (Journal of applied polymer science, 2018)
ABSTRACT A finite element method algorithm for epoxy curing degree simulation was developed in Abaqus by integrating the discretized analytical solution of the model free kinetics into its user subroutines. This method was verified by nonisothermal and isothermal DSC experiments of an epoxy resin. By means of this method, the real manufacturing press cycle could be simulated regarding temperature distribution and curing degree with advanced curing degree‐dependent material properties. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46408.